Folate biosynthesis pathway: mechanisms and insights into drug design for infectious diseases - Bertacine Dias, Marcio V. [UNESP]; Santos, Jademilson C.; Libreros-Zuniga, Gerardo A. [UNESP]; Ribeiro, Joao A.; Chavez-Pacheco, Sair M. (Future Sci Ltd, 2018)
Folate pathway is a key target for the development of new drugs against infectious diseases since the discovery of sulfa drugs and trimethoprim. The knowledge about this pathway has increased in the last years and the catalytic mechanism and structures of all enzymes of the pathway are fairly understood. In addition, differences among enzymes from prokaryotes and eukaryotes could be used for the design of specific inhibitors. In this review, we show a panorama of progress that has been achieved within the folate pathway obtained in the last years. We explored the structure and mechanism of enzymes, several genetic features, strategies, and approaches used in the design of new inhibitors that have been used as targets in pathogen chemotherapy.
Keywords: antifolate drugs; antimicrobial drugs; biosynthesis; folate pathway; microorganisms; structure-based drug discovery; tetrahydrofolate biosynthesis